The determinants that influence job performances among service counter workers at Pos Malaysia Berhad / Nor Hafiza Ahmad - Ahmad, Nor Hafiza (Faculty of Business and Management, 2011)
Recent studies have stated that the success of service organizations in general depends upon the performance of its frontline employees. Therefore, this study was conducted to examine the most dominant factor that influences job performance of service counter workers in post offices. 57 of the total employees that work in Pos Malaysia Berhad post offices around Shah Alam were the selected respondents. In finding and examining the factor, this study is based of three main research objectives. First is to identify the most dominant factor that influences the job performances of service counter workers at Pos Malaysia Berhad. Second is to examine the level of job performances among these service counter workers, and finally to study the relationship between the independent variables, which are job rotation, perceived co-worker support, reward systems and employee characteristics, with the dependent variable, job performance. In collecting the data, population design is used instead of sampling design. Data were collected through interview and survey questionnaire. In analyzing the data, reliability test, descriptive analysis and coefficient correlation was used to measure the data. Pilot study was firstly done as to test the reliability of the formulated questionnaire, and it was found that the internal consistency reliability of the measures used in the pilot study is good and acceptable. The results of the data analysis have also concluded the three research objectives. First, the most dominant factor that influences job performance is job rotation. Second, the level of performance of the service counter workers was found to be good, and finally, it was found that there is a positive relationship between job rotation, rewards and employee characteristics, with job performance. Furthermore, the findings show that there is no relationship between perceived co-worker support and job performance.